Corpus research applications in second language teaching: a look into corpus-informed materials development / Norwati Roslim ... [et al.] - Roslim, Norwati; Abdullah, Muhammad Hakimi Tew; Aziz, Anealka; Nimehchisalem, Vahid; Almuddin, Azhani (Universiti Teknologi MARA Shah Alam, 2020)
Numerous corpus studies have suggested that teaching materials design could greatly benefit from the empirical information about language use provided by corpus linguistics. In spite of the awareness that corpus-based research can offer valuable insights for materials development, still relatively small number of studies report on the practical applications of corpus data for teaching materials development. There is no clear guideline or framework on how corpora and corpus studies could assist in developing teaching materials. Hence, this study focusses on one grammatical item which poses problems to Malaysian learners, that is, prepositions. The objectives are (i) to identify prepositions in the British National Corpus as a reference corpus and the descriptions offered by linguists and grammarians as a reference grammar, and (ii) to provide a framework to use reference corpus, reference grammar and corpus-based research, as a resource for developing materials in the teaching of prepositions. In order to meet the objectives, content analysis was used as the methodology throughout this study. The findings showed that reference corpus, reference grammar and corpus-based research could be used systematically as guidance to develop corpus-informed materials. It is hoped that this contribution of knowledge could have an impact on second language learning-teaching.